Pengaruh Kelentukan Togok, Koordinasi Dan Power Otot Lengan Terhadap Hasil Pukulan Smash Pada Olahraga Bulutangkis - Marani, Ika Novitaria; Subarkah, Ari (Jurnal MensSana, 2023)
The purpose of this study was to determine whether there was an effect of waist flexibility, coordination and arm power on the smash of badminton players. The research method used in this research was correlational research. For the research subjects used was badminton athletes from Klub FIK UNJ totaling 30 people. The test instruments used in this study were: 1) to measured waist flexibility used a standing trunk flexion test, 2) to measure coordination used a throw and catch ball test on the wall, 3) to measure arm muscle power used medicine overhead. throwing test, 4) to measure the results of the smash used a smash hit accuracy test. The results showed that: there was an effect between waist flexibility toward smash with a value of tcount = 3.64 and ttable = 1.701, there was an effect between coordination toward smash with a value of tcount = 3.60 and ttable = 1.701, and there was an effect between arm muscle power toward smash with a value of tcount = 4.71 and ttable = 1.701. The conclusion of this study was that the smash of badminton players are influenced by waist flexibility, coordination and arm muscle power. Therefore, the coach must pay attention to the physical component factors that affect the results of badminton players' smash.